Caught between Aristotle and Miss Marple… – A Proposal for a Perceptual Prototype Approach to “Estuary English” - Altendorf, Ulrike (Complutense Journal of English Studies, 2017)
More than thirty years after the term was coined by David Rosewarne (1984), linguists have not come anywhere near to agreeing on a linguistically sound definition of the concept of ‘Estuary English’ (EE). Nevertheless, the term has come to stay. According to John Wells (2013), “we can now expect to be readily understood if we describe someone’s speech as ‘estuarial’”. In this paper, I will argue that ‘Estuary English’ is the name for a heuristic conceived of and popularized by linguistic laypeople and therefore defying expert linguistic analysis in terms of Aristotelian categories, even sociolinguistically “enlightened” ones. Following Taylor (2003) and Kristiansen (2008), I will suggest describing the resulting folk-linguistic category in terms of the graded structure/prototype approach. In support of the prototype hypothesis, I will present data from an on-going project in perceptual dialectology. It includes judgements of gradience of membership of 171 speakers from the South East of England, the Midlands and Scotland. Asked to rate the recordings of three young middle-class speakers from three Southeastern towns, these speaker-listeners are remarkably consistent in their responses and sometimes remarkably at odds with the analysis of expert linguists.